Det krevende spennet mellom arbeid, hjemmet og gamle hjelpetrengende foreldre En hermeneutisk studie om kvinners situasjon i skjæringspunktet mellom yrkesliv og dobbelt omsorgsansvar - Berthinussen, Ingrid S.; Fredriksen, Sven-Tore Dreyer (Nordisk tidsskrift for helseforskning, 2014)
The aim of this study is to describe how women experience the difficult balancing act of caring for old and frail parents, managing their professional careers and taking care of their own families. Life expectancy has increased in the western world since World War Two, leading to an increasing number of elderly, and elderly with health problems, in need of care and assistance. Additional, health care reforms reguire the elderly to continue to live in their own homes for as long as possible. Traditionally the daughters often end up with carrying the heaviest load of caring for their parents, with all emotional and physical strains entailed, these two facts creates an additional burden on top of t their regular responsibilities regarding family life and career. A qualitative approach was used which includes deep interweaves and hermeneutic analysis. Analyzing the present material we come up with seven sub-themes, and these seven sub-themes crystallized into three main themes: the moral obligations, the anguish and feelings and personal health.
Keywords: Pårørende; yrkesaktive; kvinners trippelrolle; omsorgsrolle og gamle hjelpetrengende foreldre; Relatives; career women´s triple role; nursing and caring; old and frail parents